A post-transformational study of phrasal possessive constructions in English - Lutfi, Abbas Fadil; Ahmad, Salih Ibrahim (ZANCO Journal of Human Sciences., 2018)
This paper observes the three modules of government-binding (henceforth GB) theory which come into existence after transforming a syntactic string from D-structure to S-structure level. Transforming a syntactic structure via the process of movement leads to the appearance of a new structure, which is different from the original one at D-structure level. Here the focus is on the phrasal possessive constructions to which bounding (movement) theory, government theory, and binding theory are applied. The paper tries to provide a possible answer to the question of whether there is any relationship between the three post-transformational modules or not with respect to possessives. Also, and more importantly, it aims at indicating the extent to which possessives adhere to the modules. The paper is a theoretical one whose data is from textbooks and scholarly articles, rather than from participants. One of the outstanding conclusions is that the two modules of government theory and binding theory are highly intertwined due to sharing the structural relation of c-command.